In Silico Interaction Study of the Hydrazine Compound as an Antibody Drug Conjugate Linker Against Pertuzumab - Ananda, Lintang Tri; Rizkita, Aden Dhana; Gibran , Syahrul Syah; Shapira, Shari Bella; Nour baety, Shelly Siti; Wafa, Shahibatul; Oksal, Efriyana (Indonesian Journal of Chemical Science, 2025)
Breast cancer can be initiated, one way or another, by overexpression of the HER-2 protein which can induce dimerization, resulting in metastasis in breast cancer cells. Pertuzumab is one of the methods used to treat metastatic breast cancer that is breast cancer cells that the cancer has spread to other parts of the body. Hydrazine is something hydro nitrogen compounds that has the formula N2H4 molecule. The hydrazine compound has chemical characteristics as a strong reducing agent because hydrazine plays a role as donor group hydrogen can reduce double bonds into single bonds through reaction hydrogenation. Research purposes This is o see the bond between Hydrazine as a linker with pertuzumab as an antibody for development of Antibody Drug Conjugate in silico with molecular docking. The docking method is used to know the conformation and free energy ties involved in the interaction between molecule (pertuzumab) and its ligand (hydrazine). In silico molecular docking was carried out with a number of stages such as ligand preparation, preparation of macromolecules, validation molecular docking method, docking hydrazine with pertuzumab protein and intermediate data analysis optimized hydrazine compound with which pertuzumab protein the lower mark energy bond so the stronger and stable the bond that occurs between hydrazine compound and pertuzumab protein . Obtained the result of docking is in the form of binding affinity from the results of addition of pertuzumab protein with the hydrazine ligand which is -6.8 which shows conformation formed stable or does not require great energy To do binding. Visualization results from complex molecule hydrazine compound against pertuzumab protein own identical confirmation on the part side active binding from pertuzumab protein macromolecules . The hydrazine compound can be bonded with pertuzumab and has potential as a new drug development in the targeting antibody drug conjugate breast cancer.